(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
We use an R&D network model by Goyal and Moraga-Gonzalez [13] to maximize the equilibrium outcomes. We focus on the effectiveness of R&D expenditures and its effect on the outcomes. We find that characteristics of markets and networks influence values of the effectiveness. The change of this parameter has a negative impact on the individual and social outcomes.